2010
DOI: 10.2175/193864710798217115
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution, Count Rate, and Membrane Fouling in Hollow-Fiber Microfiltration

Abstract: Membrane processes are a widely used and a growing method to reclaim wastewater effluent.However, a major drawback is their energy intensity. Treating 1 million gallons of water requires in general 600-800 kW for microfiltration and 1,600-2,000 kW for reverse osmosis membranes.A better understanding of membrane fouling is key to reducing energy requirements, which in turn lower running costs. There are two fouling mechanisms: 1) the more known type is cake formation on the membrane caused by particles greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Better understanding of membrane fouling is one of the key in reducing the operational problems and operating costs in MBR plants. Smeraldi et al (2010) reported that membrane fouling in hollow fiber membrane can be attributed to pore plugging caused by biogenic nanoparticles (< 0.2 microns), which have a higher potential to foul due to their smaller size, and account for 80% of flux reduction, causing irreversible fouling that necessitates costly chemical cleaning.…”
Section: Stone and Livingstonmentioning
confidence: 99%
“…Better understanding of membrane fouling is one of the key in reducing the operational problems and operating costs in MBR plants. Smeraldi et al (2010) reported that membrane fouling in hollow fiber membrane can be attributed to pore plugging caused by biogenic nanoparticles (< 0.2 microns), which have a higher potential to foul due to their smaller size, and account for 80% of flux reduction, causing irreversible fouling that necessitates costly chemical cleaning.…”
Section: Stone and Livingstonmentioning
confidence: 99%